2008
DOI: 10.1152/ajpregu.00421.2007
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and sex differences in small mesenteric arteries of the estrogen receptor-β knockout mouse

Abstract: The role of the estrogen receptor (ER) subtypes in the modulation of vascular function is poorly understood. The aim of this study was to characterize ex vivo the functional properties of small arteries and their response to estrogens in the mesenteric circulation of female and male ER-beta knockout mice (beta-ERKO) and their wild-type (WT) littermates. Responses to changes in intraluminal flow and pressure were obtained before and after incubation with 17beta-estradiol or ER-alpha agonist propyl-pyrazole-trio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 51 publications
3
7
1
Order By: Relevance
“…For example, only the selective ER␣ agonist, DPN, induces acute NOdependent vasodilation (Bolego et al, 2005). Likewise, in small mesenteric arteries from female mice, PPT increased flow-mediated relaxation; interestingly, there was no effect of PPT in arteries from males (Douglas et al, 2008). These studies using selective ER agonists support the conclusion that ER␣ is the principal form 214 MILLER AND DUCKLES involved in mediating the actions of estrogen on vascular function.…”
Section: A Effects On Gene Transcriptionmentioning
confidence: 68%
“…For example, only the selective ER␣ agonist, DPN, induces acute NOdependent vasodilation (Bolego et al, 2005). Likewise, in small mesenteric arteries from female mice, PPT increased flow-mediated relaxation; interestingly, there was no effect of PPT in arteries from males (Douglas et al, 2008). These studies using selective ER agonists support the conclusion that ER␣ is the principal form 214 MILLER AND DUCKLES involved in mediating the actions of estrogen on vascular function.…”
Section: A Effects On Gene Transcriptionmentioning
confidence: 68%
“…Note that female animals were selected for these studies so as to maximize responses. However, 1) since male animals also express ERs in the vasculature (13,18), 2) since it is now recognized that ER-␣ contributes to physiological function in the male vasculature (9,27), and 3) since our prior studies in male compared with female vascular smooth muscle cells showed similar responses for Resv (14), we expect similar responses in male mice. In studies involving a pharmacological inhibition of NOS, the mice were administered N G -nitro-L-arginine methyl ester (L-NAME, 50 mg/kg) in their drinking water, starting 7 days before the denudation procedure, continuing through 14 days postdenudation.…”
Section: Animals Female Er-␣mentioning
confidence: 89%
“…Studies with selective ER agonists suggest that ERα may mediate most of the vascular actions of estrogen. PPT increases flow-mediated relaxation in small mesenteric arteries from female, but not male mice [64]. Diarylpropionitrile (DPN) is a potent ERβ agonist with a 30- to 70-fold selectivity over ERα [41].…”
Section: Selective Er Agonists and Antagonistsmentioning
confidence: 99%